Professional Quality of Life: Frontline and Non-frontline Workers of Sukraraj Tropical and Infections Disease Hospital - Kafle, Ashish; Thapaliya, Amee (JMC Research Journal, 2020)
During the coronavirus pandemic health care workers are one of the most at risk of infection and work-related stress, which can have negative impact on their professional quality of life. A cross-sectional study was conducted at Sukraraj Tropical and Infections Disease Hospital where professional quality of life was examined among 89 healthcare providers. This study showed high level of compassion satisfaction, low level of burnout, moderate level of secondary traumatic stress. When using Mann-Whitney U-test, significant difference between frontline (Median=20) and non-frontline (Median=17) workers regarding burnout (p < 0.05) was observed, no significant difference was observed among frontline (Median=43) and non-frontline (Median=47) workers regarding compassion satisfaction, and secondary traumatic stress frontline workers (Median=26) and non-frontline workers (Median=23). This study showed that the frontline workers and non-frontline workers were dealing well with the pandemic situation. However, as the pandemic continues further with increasing cases, increase in burnout and secondary stress, along with decrease in compassion satisfaction is probable. As such, timely preventive psychological intervention would be beneficial for overall professional quality of life of healthcare workers.